Menelaah Ulang Peran Roh Kudus dan Pengaruhnya terhadap Umat Kristen Masa Kini (International Forum of Researchers and Lecturers, 2025)
This research examines the crucial role of the Holy Spirit in the spiritual growth and ministry of contemporary Christians, considering that many have not actively experienced His involvement, resulting in low spiritual quality. Its objective is to re-examine the Holy Spirit's influence for a clearer understanding. Employing a qualitative library research method with textual analysis of the Bible and theological literature (hermeneutics), this study finds that the Holy Spirit is a divine person actively guiding, transforming character, and serving as Creator, Reconciler, and Redeemer. The Pentecost event demonstrates initial empowerment. Spiritual gifts are an expression of His role, which, though debated, function to equip ministry, strengthen community, and facilitate evangelism. The Holy Spirit is also a source of character transformation and empowerment for mission. Baptism in the Holy Spirit becomes a moment of life change and sanctification. The implication is that a clear understanding and open attitude towards the Holy Spirit are essential for unity, church growth, and glorifying Christ.